(3CdajI GdYQGbi aj Ydhe GdMOjKs - (3YHO GdQMje Hf GdMSjf Hf YHO GdQMef, CHh GdaVd, Rjf GdOjf, GdMGaX GdYQGbj, J (B806 (3g`s ((3Ydi Hf YHO Gddg Hf Ydi Hf QGhY s)
(3ChdgG (B:s
(3jbhd QGLi QHg GdebJOQ YHO GdQMje Hf GdMSf GdCKQi ef HYO MeO Gddg Pi GdCdGA Ydi EeJfGf Ld Yf EMUGA s
(3BNQgG (B:s
(3hQHfG GdeMehO hGdeTchQ Edjg efG JQLY GdCehQ hCaVd GdUdGI hGdSdGe Ydi efG JQLY GdCehQ cedJ GdfSNI GdeHGQcI HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B344s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs